A new species of the genus Isoperla (Plecoptera: Perlodidae) from TIANMU MOUNTAIN NATURE RESERVE, China - Huo, Qing-Bo; Du, Yu-Zhou (Zootaxa, 2018)
A species of the genus Isoperla Banks, 1906, I. oncocauda Huo & Du, sp. nov. is described as new to science and is the first record for the family Perlodidae from the Tianmu Mountain Nature Reserve, Zhejiang Province of eastern coastal China. Both sexes of the new species are characterized by tergum 10 with a developed process. The partially extruded aedeagus of the male is membranous without conspicuous larger sclerites and with the ventral surface covered with dense scale-like and nail-shaped spines.